Human capital and firms’ markup: evidence from China - Wen Yue (Journal of Applied Economics, 2022)
Based on the university enrollment expansion policy implemented by the Chinese government in 1999, I use the difference-in-difference method to explore the effects of human capital expansion on firms’ markup and the influencing mechanism. Findings suggest that human capital expansion significantly promotes the improvement of firms’ markup, which remains true after a series of robustness tests. The analysis of the influencing mechanism shows that on the one hand, human capital expansion promotes the improvement of firms’ production efficiency and improves their markup through the production efficiency channel. On the other hand, human capital expansion improves the market pricing power of firms and exerts a significant positive impact on their markup through the market pricing channel. Further analysis also shows the varying impacts of human capital expansion on the markup of different types of firms. This study enhances the understanding of the microeconomic effects of human capital expansion from the markup perspective.